Carbon dots as naked eye sensors. Issue 8 (16th March 2021) - Junaid, Hafiz Muhammad; Solangi, Amber Rehana; Batool, Madeeha
Abstract : Optical sensors are always fascinating for chemists due to their selectivity, sensitivity, robustness and cost-effective nature. Abstract : Optical sensors are always fascinating for chemists due to their selectivity, sensitivity, robustness and cost-effective nature. Moreover, these sensors provide the facility of onsite detection without employing any instrumental technique. A number of such visual sensors including carbon dots (CDs) have been reported for selective detection of many ionic and molecular species. This review elaborates the utilization of CDs as colorimetric sensors. Carbon dots (CDs) are being synthesized from a large number of natural and synthetic carbon source materials using a variety of methods. CDs can also be tuned chemically by doping, to impart the desired sensing properties. Therefore, the development of CDs with selective sensing properties enables extremely low detection limits and has thus gained substantial attention.